Socioecological disparities in New Orleans following Hurricane Katrina - Lewis, Joshua A.; Zipperer, Wayne C.; Ernstson, Henrik; Bernik, Brittany; Hazen, Rebecca; Elmqvist, Thomas; Blum, Michael J. (Ecosphere (Washington, D.C), 2017)
Despite growing interest in urban resilience, remarkably little is known about vegetation dynamics in the aftermath of disasters. In this study, we examined the composition and structure of plant communities across New Orleans (Louisiana, USA) following catastrophic flooding triggered by levee failures during Hurricane Katrina in 2005. Focusing on eight neighborhoods that span a range of demographic and topographical conditions, we assessed whether plant communities in post‐Katrina New Orleans reflect flooding disturbance and post‐disaster landscape management policies. We then contextualized vegetation patterns and associated ecosystem services and disservices with census‐based demographic trends and in‐depth interviews to draw inferences about the drivers and outcomes of urban land abandonment in the aftermath of Hurricane Katrina. We found that areas subject to the greatest flooding disturbance exhibit the highest rates of vegetation response. Disturbance intensity and elevation, however, are relatively weak drivers of vegetation differences among the studied neighborhoods. Rather, we found that household income, racial demographics, and land abandonment are important drivers of vegetation community composition and structure across the city. Our findings indicate that resettlement and landscape management policies can mediate post‐flooding ecological outcomes and demonstrate that unmanaged, emergent vegetation on abandoned lands can be an environmental justice concern in underserved and historically marginalized communities.